(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article reveals the reasons for the success of the United States in developing new economic growth points and new development models such as cloud computing, the Internet, artificial intelligence, and the sharing economy. Examples of internationally renowned new technology companies are given. The article presents a picture of the evolution of legislative regulation of startups, which dates back to the beginning of the 20th century – starting with the adoption of the Securities Act (1930s) and ending with the legal basis of Crowdfunding and new technologies. An assessment of the regulatory framework is given, and lessons are formulated for developing countries and countries in transition in the formation of a legislative and legal framework for startups.